Detection of the lunar body tide by the Lunar Orbiter Laser Altimeter. Issue 7 (4th April 2014) - Mazarico, Erwan; Barker, Michael K.; Neumann, Gregory A.; Zuber, Maria T.; Smith, David E.
Abstract : The Lunar Orbiter Laser Altimeter instrument onboard the Lunar Reconnaissance Orbiter spacecraft collected more than 5 billion measurements in the nominal 50 km orbit over 10, 000 orbits. The data precision, geodetic accuracy, and spatial distribution enable two‐dimensional crossovers to be used to infer relative radial position corrections between tracks to better than 1 m. We use nearly 500, 000 altimetric crossovers to separate remaining high‐frequency spacecraft trajectory errors from the periodic radial surface tidal deformation. The unusual sampling of the lunar body tide from polar lunar orbit limits the size of the typical differential signal expected at ground track intersections to 10 cm. Nevertheless, we reliably detect the topographic tidal signal and estimate the associated Love number h 2 to be 0.0371 ± 0.0033, which is consistent with but lower than recent results from lunar laser ranging. Key Points: Altimetric data are used to create radial constraints on the tidal deformation The body tide amplitude is estimated from the crossover data The estimated Love number is consistent with previous estimates but more precise